Early MicroRNA Expression Profile as a Prognostic Biomarker for the Development of Pelvic Inflammatory Disease in a Mouse Model of Chlamydial Genital Infection - Laxmi Yeruva (American Society for Microbiology, 2014)
ABSTRACT It is not currently possible to predict the probability of whether a woman with a chlamydial genital infection will develop pelvic inflammatory disease (PID). To determine if specific biomarkers may be associated with distinct chlamydial pathotypes, we utilized two Chlamydia muridarum variants (C. muridarum Var001 [CmVar001] and CmVar004) that differ in their abilities to elicit upper genital tract pathology in a mouse model. CmVar004 has a lower growth rate in vitro and induces pathology in only 20% of C57BL/6 mouse oviducts versus 83.3% of oviducts in CmVar001-infected mice. To determine if chemokine and cytokine production within 24 h of infection is associated with the outcome of pathology, levels of 15 chemokines and cytokines were measured. CmVar004 infection induced significantly lower levels of CXCL1, CXCL2, tumor necrosis factor alpha (TNF-α), and CCL2 in comparison to CmVar001 infection with similar rRNA (rs16) levels for Chlamydiae. A combination of microRNA (miRNA) sequencing and quantitative real-time PCR (qRT-PCR) analysis of 134 inflammation-related miRNAs was performed 24 h postinfection to determine if the chemokine/cytokine responses would also be reflected in miRNA expression profiles. Interestingly, 12 miRNAs (miR-135a-5p, miR298-5p, miR142-3p, miR223-3p, miR299a-3p, miR147-3p, miR105, miR325-3p, miR132-3p, miR142-5p, miR155-5p, and miR-410-3p) were overexpressed during CmVar004 infection compared to CmVar001 infection, inversely correlating with the respective chemokine/cytokine responses. To our knowledge, this is the first report demonstrating that early biomarkers elicited in the host can differentiate between two pathological variants of chlamydiae and be predictive of upper tract disease. IMPORTANCE It is apparent that an infecting chlamydial population consists of multiple genetic variants with differing capabilities of eliciting a pathological response; thus, it may be possible to identify biomarkers specific for a given virulence pathotype. miRNAs are known to regulate genes that in turn regulate signaling pathways involved in disease pathogenesis. Importantly, miRNAs are stable and can reflect a tissue response and therefore have the potential to be biomarkers of disease severity. Currently, with respect to chlamydial infections, there is no way to predict whether an infected patient is more or less likely to develop PID. However, data presented in this study indicate that the expression of a specific miRNA profile associated with a virulent variant early in the infection course may be predictive of an increased risk of pelvic inflammatory disease, allowing more aggressive treatment before significant pathology develops.